Sharing Authority Between Licensing Decentralization and Rights Deconcentration in Water Space Management - Dzulkarnain Alghafuru Syahputra; Indrawati Indrawati (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the problem of authority over the management of water space in Indonesia, which is caught between the tension of licensing decentralization and the need for decentralization of rights determination. The research method used was normative legal research with a legislative, conceptual, and study approach of Constitutional Court Decision Number 3/PUU-VIII/2010. The novelty in this research is the proposed model of authority sharing that clearly distinguishes between administrative licensing decentralization and property rights determination deconcentration, accompanied by institutional synchronization, integrated digital licensing systems, improved central-regional incentive structures, and strengthened mechanisms for community rights recognition and meaningful public participation. Based on the research, it is concluded that: first, decentralization of licensing is important for efficiency and proximity of services, but must be selective because it risks policy fragmentation, elite capture, and inter-regional conflicts; second, the establishment of exclusive property rights over water areas that have long-term impacts and affect public access requires stronger state control through deconcentration mechanisms, as emphasized by the Constitutional Court Decision that invalidated the HP-3 concept. The research recommends an authority-sharing model with institutional synchronization between the Ministry of Marine Affairs and Fisheries and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, the development of an integrated digital licensing system, improvement of the central-regional incentive structure, and strengthening of community rights recognition and meaningful public participation.